Feasibility Study of Coal Gasification Business into Dimethyl Ether (DME) with Cost Benefit Analysis (CBA) Method to Support National Energy Security - Saleh, Basuki Rahmad; Saputro, Guntur Eko; Hidayatullah, Syarif; Sujana, Ahmad (International Journal of Economics Development Research (IJEDR), 2025)
The coal gasification project for Dimethyl Ethane (DME) in Indonesia offers great potential to support the energy transition by reducing dependence on energy imports, saving the country's foreign exchange, and contributing to reducing greenhouse gas emissions. Through a Cost-Benefit Analysis (CBA), this study assesses the economic feasibility and environmental consequence of the project, focusing on investment costs, foreign exchange savings, emission reductions, and job creation. Although the project promises significant benefits, key challenges include high investment costs, dependence on foreign technology, and the sustainability of environmentally friendly coal supplies. Therefore, the project's success is highly dependent on supportive policies, such as fiscal incentives, public-private partnerships, and strengthening domestic technology research, which can ensure a cleaner and more sustainable energy transition in Indonesia.